TRADISI PEUSIJUEK SEBAGAI SARANA MEDIASI DITENGAH SYARIAT ISLAM DI ACEH - Nanda Septi Prayetno (Prodi Studi Agama-Agama, 2021)
The purpose of this research is to find out how the peusijuek tradition act as a media means in the mix of Islamic syaria law in districts of Kuta Baro Aceh Besar Region in the Aceh Province. And how the peusijuek tradition functions in society for it to be able to last until now in the presence of the assumption that the peusijuek tradition is a hindu tradition and considered a bid’ah and not according to the syaria law. This research uses the descriptive qualitative method, where the researcher gains the information straight from the result of interview and literature review. During the course of this research, the researcher uses the cultural functionalism theory according to Malinowski. Functionalistic theory explains that between the elements of a culture, there is a link, and why certain patterns happen or at least why the patterns still lasts and claimed by the society. Regardless it does not stray from the function that the culture has, like the peusijuk tradition that lives and color the social lives of Acehnese people. The peusijeuk tradition is an embodiment of gratefulness to Allah SWT for what have been obtained in someones life that is implemented in forms of ceremony. The peusijuek tradition is also a way to manifest peace in social life of the Kuta Baro district. The result form this research is to state that the peusijuek tradition as a media means in the mix of Islamic syaria law that has a very important role for the society, because it has a certain function, which is to bring prosperity, to expect blessing, to keep peace between people, and to protect and maintan the culture. To this day the peusijuek tradition is a social reality and also to become an identity of the Acehnese people, especialy to the Kuta Baro Kabupaten Aceh Besar district.